Dėl baltų *pat(is), *pat(n)ī pirminės reikšmės ir gramatinio statuso - Rosinas, Albertas (Baltistica, 2000)
ON THE ORIGINAL MEANING AND THE GRAMMATICAL STATUS OF BALTIC *pat(is), *pat(n)īOn the basis of the data from the Baltic and other Indo-European languages, the article rejects the common current view that Baltic *pat-root nouns, cf. Latv. pats ‘master, mister, husband’, pati ‘mistress, wife’, evolved from *pat-root pronouns with the meaning of ‘self’. The data from the Baltic languages lead to the conclusion that from Proto-Indo-European the Proto-Balts inherited the root noun of the consonantal declension *pat (Lith. patì, Latv. pati). The assumption that the Baltic nouns *patis, *patnī did not evolve from pronouns could be supported by the following: (a) i-stem resp. C-stem pronominal paradigms are not characteristic of the Baltic pronominal systems; (b) moreover, the Prussian language (like the German, Slavonic and Indo-Iranian languages) never possessed *pat-root pronouns.In the East Baltic languages, pronouns with the meaning of ‘self’ evolved from the nouns *pat(is), *pat(n)ī in the process of pronominalization, which originally occurred in the sphere of the addressee and the non-participant person. In the process of pronominalization, *pat(is) eventually acquired endings typical of pronouns, cf. dat. sing, pačiam
Keywords: baltų kalbos; pat